Methodology of technical evaluation on field of water injection pilot projects - Sánchez Toapanta, Bryan (2022)
The purpose of this document is to evaluate the water injection pilot projects implemented as part of the secondary recovery expansion project in the Shushufindi oilfield through the technical monitoring on field of the production parameters that allow identifying the influence of the project in the production wells during 2019-2020. The methodology used is based on the control and monitoring of the data obtained on field, which allows identifying if there is variation in the behavior of the production or injection parameters. For the development of this study, the water injection performance was evaluated, using the Hall plot and injectivity index of each injector well. Moreover, the production parameters of the selected wells near the influence area were analyzed. Among the parameters that were evaluated were: salinity, pressures, flow rates, electrical submersible pump parameters, and workovers carried out during the evaluation period. Once the evaluation of the injection influence was completed, it was determined whether the maintenance of the production is related of the water injection or other types of work performed during the evaluation period.